ナンキョク ショウワキチ ダイ10 キョジュウトウ ノ ユセイ コーキングザイ オヨビ ゴム カンジョウ ガスケット ノ ケイネン ヘンカ ト タイキュウセイ - 田中, 亨二; タナカ, キョウジ; 清水, 市郎; シミズ, イチロウ; 須田, 祐子; スダ, ユウコ; Tanaka, Kyoji; Shimizu, Ichirou; Suda, Yuko (2002)
P(論文) 昭和基地の第10居住棟壁材の目地に施工され、29年経過した油性コーキング材・ゴム環状ガスケットの劣化性状について調査を行った。調査は、油性コーキングについては指触試験・針入度試験、並びにゴム環状ガスケットについては外観観察・引張試験・硬さ試験を行い、それぞれ劣化性状について検討を行った。その結果、油性コーキング材については、硬く脆化し機能を果たしてはいないが、パネルが動かない、2次シール材が設けられていた等の理由で故障等は顕在化しなかった。また、ゴム環状ガスケットについては、力学的・形状的には実用上の使用には耐えられるが、亀裂の激しい部分もあり使用限界であると思われた。 Deterioration of aged oil-based caulking and rubber gaskets that had been used for sealing in the joints between wall panels of the old living hut built in 1969 at Syowa Station was studied. As for oil-based caulking, tack and penetration measurements were carried out. The caulking turned from flexible to brittle in mechanical property by degradation. Fortunately, no water leakage from the joints was reported in the service period of the building though the material had not severely moved by rigid structural design. As for rubber gaskets, appearance observation, tensile and hardness tests were carried out, they keep at good level in mechanical property, however severe cracks occurred on their surfaces, and they were judged to have reached the limit of their useful lifetimes. departmental bulletin paper